Florida's Introduced Birds: Purple Swamphen (Porphyrio porphyrio) - Steve A. Johnson; Monica McGarrity (EDIS)
WEC270, a 6-page illustrated fact sheet by Steve A. Johnson and Monica McGarrity, is part of the Florida's Introduced Birds series. It describes this shy wetland bird accidently released into the wild during Hurricane Andrew — similar species, native ranges and habitats, mode of introduction, introduced range and habitats, ecology, ecological impacts, impacts to people and pets, solutions, and how you can help. Includes additional resources. Published by the UF Department of Wildlife Ecology and Conservation, November 2009.